Brazilian Truth Commissions as Experiments of Representation: Between Impartiality and Proximity. Issue 3 (3rd July 2019) - Hollanda, Cristina
ABSTRACT: The establishment of the National Truth Commission (NTC) in Brazil investigated human rights violations perpetrated by the civil–military dictatorship and triggered the subsequent creation of a large number of sub-national truth commissions. These commissions were established in myriad ways, but they are all non-elected bodies that lack traditional voters' authorisation and accountability mechanisms at their inception. Nonetheless, their actors have created a large body of representative claims to support their actions, the examination of which is the purpose of this article. The analysis is based on data collected by the author, including interviews with commissioners. There is a widespread agreement about the ethical objectives of human rights advocacy and the shared assumption that exposing the "truth" about the violent past is a means to achieve these objectives. Conversely, there is substantial disagreement about the driving values behind the commissions, which can to some extent be described by the notions of active impartiality, proximity and perspective . I conclude that the fundamental shared trait of the representative claims deployed by the sub-national truth commissions in Brazil involves conceptualising victims as legitimate representatives, who are qualified by the moral authority of their experience, in contrast with other national truth commissions.